Assessment of sources for higher Uranium concentration in ground waters of the Central Tamilnadu, India - Adithya, V.; Chidambaram, S.; Tirumalesh, K.; Thivya, C.; Thilagavathi, R.; Prasanna, Mohan Viswanathan (2016)
The uranium concentration in groundwater has attained greater importance considering the health effects in mankind. Groundwater being the major source of uranium; sampling and analysis of groundwater for the major cations and anions along with uranium has been carried out in hard rock aquifers of Madurai district. The sampling has been carried out in varied aquifers like, Charnockites, Hornblende Biotite Gneiss, Granites, Quartzites, Laterites and sandstone. The cation and anions showed the following order of dominance Na+>Ca2+>Mg2+>K+ and that of anions are HCO3->Cl->SO42-> NO3->PO43-. Higher concentration of uranium was found along the granitic aquifers and it varied along the groundwater table condition. Further it was identified that the mineral weathering was the predominant source of U in groundwater. Tritium studies also reveal the fact that the younger waters are more enriched in uranium than the older groundwater with longer residence time.